INDUKSI TUNAS ANGGREK (Dendrobium sp) Var. Kumala MENGGUNAKAN BAP (6-Benzyl Amino Purine) DAN AIR KELAPA SECARA IN-VITRO - Reni Annisa Nurhanifah; Ateng Supriyatna; Ayuni Adawiyah (Gunung Djati Conference Series, 2021)
Orchid plants are one type of ornamental plant that has a unique flower beauty and a long flower life compared to other flower plants. The beauty and attractiveness of orchids lies in the various shapes and colors of their flowers. because this Dendrobium orchid has the potential as an ornamental plant so that it is widely developed and propagated in Indonesia because the climate is very suitable for growing orchids. This study aimed to determine the effect of BAP (6-Benzyl amino purine) and coconut water on the growth of orchid explants in vitro and to determine the optimum concentration of the combination of BAP and coconut water on the growth of orchid explants in vitro. The method used is the Completely Randomized Design (CRD) method using MS media, there are 10 concentration variations where 1 control concentration and 9 concentrations of BAP and coconut water combination. Each treatment consisted of 3 repetitions. Thus, 30 experimental units were obtained. The results showed that MS media using a combination of 1.5 ppm BAP and 200 ml of coconut water could trigger the growth of leaves, 0.5 ppm BAP treatment plus 150 ml of coconut water could trigger stem elongation and shoot number, while the control treatment can trigger the growth of the number of roots. The survival percentage is 100% where none of the 30 ripening bottles is contaminated.